Somalian women with female genital mutilation had increased risk of female sexual dysfunction: a cross-sectional observational study - Abdikarim Hussein Mohamed; Rahma Yusuf Haji Mohamud; Hussein Ali Mohamud; Aşır Eraslan; Metin Gur; Abdikarim Ali Omar; Sertac Cimen (Scientific Reports, 2022)
Abstract Studies regarding the impact of female genital mutilation/cutting (FGM/C) on sexual function are scarce. This study is the first to explore the rate of female sexual dysfunction (FSD) among Somalian women who underwent FGM and its association with different FGM types. This study was carried out among women with a history of FGM who visited our clinic for a medical check-up. It relied on data including socio-demographic features, type of FGM determined by an examination, and the Female Sexual Function Index (FSFI) scores. Overall, 255 women were included. While 43.9% (n = 112) of the respondents had a history of Type 3 FGM, 32.2% had Type 2 (n = 82), and 23.9% had Type 1 (n = 61) FGM. Among all patients, 223 had FSD (87.6%). There was a significant association between the FGM type and FSD (p < 0.001). The mean total FSFI score for the patients with Type 1, 2, and 3 FGM was 22.5, 19.7, and 17.3, respectively, all indicating FSD. The FSD is prevalent among mutilated Somalian women. Patients with Type 3 FGM had the lowest mean total FSFI scores indicating that the impact on sexual function was correlated with the extent of tissue damage during FGM.